Simulated Annealing Based Strategy for Test Redundancy Reduction - Kamal Z., Zamli; Mohd Hafiz, Mohd Hassin; Al-Kazemi, Basem; Naseer, Atif (2014)
Software testing relates to the process of accessing the functionality of a program against some defined specifications. To ensure conformance, test engineers often generate a set of test cases to validate against the user requirements. When dealing with large line of codes (LOCs), there are potentially issue of redundancies as new test cases may be added and old test cases may be deleted during the whole testing process. In order to address this issue, we have developed a new strategy, called tReductSA, to systematically minimize test cases for testing consideration. Unlike existing works which rely on the Greedy approaches, our work adopts the random sequence permutation and optimization algorithm based on Simulated Annealing with systematic merging technique. Our benchmark experiments demonstrate that tReductSA scales well with existing works (including that of GE, GRE and HGS) as far as optimality is concerned. On the other note, tReductSA also offers more diversified solutions as compared to existing work.